Reflections of sexual harassment on psychology and media - Çıvgın, Umut (IGI Global, 2022)
In this chapter, the aim is to discuss what sexual harassment is, theoretical models based on sexual harassment, social and individual effects of sexual harassment, and the place of sexual harassment in the media. This chapter consists of three main sections. Firstly, sexual harassment is defined, and the theoretical models related to sexual harassment, gender differences in sexual harassment, and world statistics on sexual harassment are introduced. In the second part, the effects of sexual harassment on the society and the individual are examined from the perspective of psychology. In addition, the psychological consequences of sexual harassment at the individual level are examined from the perspective of clinical psychology. The last section covers the impact and visibility of sexual harassment on the media and the social media visibility examples of sexual harassment. © 2023, IGI Global. All rights reserved.